2013
DOI: 10.7546/cr-2013-66-6-13101331-14
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Acutely Applied Cannabinoid CB1 Ligands on Nociception in Rats with a Model of Depression

Abstract: The effects of CB1 receptor agonist HU-210 and cannabinoid CB1 receptor antagonist SR 141716A on nociception of male Wistar rats with a model of depression (bilateral olfactory bulbectomy, OBX) were studied. HU-210 (5 ñg) and SR 141716A (3 ñg) were acutely microinjected i.c.v. on the developed depression background. Nociception was examined as applied mechanical pressure on the left hind paw of the rat (analgesy-meter test, Randall & Sellitto). In the OBX rats, it was found that the pain threshold was increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 10 publications
2
4
0
Order By: Relevance
“…Yamamoto et al (1997) suggested that attention deficit is involved in the memory impairment of OBX rats tested in 3-lever operant task. The effects of the CB1 agonist on the avoidance behavior are similar to the ones previously reported upon an acute i.c.v injection, where HU 210 improved the scores of the OBX rats in both avoidance tasks and impaired the performance of the sham group (Marinov et al, 2013). Unlike the acute treatment, where SR 141716A enhanced the avoidance learning of sham rats in TWAA only, the subchronic treatment enhanced memory of the sham group (both tasks) and showed a tendency to exacerbate memory deficits of the OBX rats in TWAA.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Yamamoto et al (1997) suggested that attention deficit is involved in the memory impairment of OBX rats tested in 3-lever operant task. The effects of the CB1 agonist on the avoidance behavior are similar to the ones previously reported upon an acute i.c.v injection, where HU 210 improved the scores of the OBX rats in both avoidance tasks and impaired the performance of the sham group (Marinov et al, 2013). Unlike the acute treatment, where SR 141716A enhanced the avoidance learning of sham rats in TWAA only, the subchronic treatment enhanced memory of the sham group (both tasks) and showed a tendency to exacerbate memory deficits of the OBX rats in TWAA.…”
Section: Discussionsupporting
confidence: 85%
“…While the activation of the CB1 receptor by agonists has been found to predominantly improve the depressive-like state in animal models (Segev et al, 2014;Kruk-Slomka et al, 2015;Haj-Mirzaian et al, 2017), the data on the role of CB1 antagonists are contradictory. Previously, we have demonstrated impaired performance of OBX rats in both active and passive avoidance tests (Tashev et al, 2010) and modulatory effects of acutely i.c.v applied CB1 ligands on the performance of OBX rats in these tests (Marinov et al, 2013).…”
Section: Introductionmentioning
confidence: 73%
“…In the present study HU-210 showed a memory improving effect on the memory deficits of OBX rats, expressed as an increase of the latent time on 3 rd and 24 th hour of the retention test and an increase of the rats that reached the learning criteria, while SR 141716A did not produce any significant effects on rats performance. These findings are consistent with our previous research on the effects of cannabinoid ligands on the performance of OBX-rats in an active-avoidance test (shuttle box) (19). A positive effect, improving the locomotor deficits induced by the bulbectomy has been reported by Rodríguez-Gaztelumendi et al (25) after acute intraperitoneal administration of Δ 9tetrahydrocannabinol.…”
Section: Discussionsupporting
confidence: 92%
“…As far as olfactory bulbectomy reduces the nociceptive response of rats in the analgesy-meter test, the effect of HU-210 could be interpreted as a tendency for an improvement of the nociceptive response. 16,17 Previously we have found similar effects upon acute icv injection of HU-210 and SR 141716A. 17 Recently, it has been shown that cannabinoids play a role in nociceptive processes although the exact mechanisms by which they interfere in these processes are not well established.…”
Section: Discussionmentioning
confidence: 73%
“…16,17 Previously we have found similar effects upon acute icv injection of HU-210 and SR 141716A. 17 Recently, it has been shown that cannabinoids play a role in nociceptive processes although the exact mechanisms by which they interfere in these processes are not well established. [18][19][20][21]…”
Section: Discussionmentioning
confidence: 76%